2016
DOI: 10.3945/ajcn.115.118000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of community-based sales of micronutrient powders on morbidity episodes in preschool children in Western Kenya

Abstract: Background Although the use of micronutrient powders (MNPs) is considered the preferred approach for childhood anemia control, concerns about iron-related morbidity from clinical trials have challenged programmatic scale-up. Objective We aimed to measure the effects of community-based sales of MNPs on diarrhea-, fever-, cough-, and malaria-morbidity episodes in children 6–35 mo of age. Design We conducted a cluster-randomized trial in rural Western Kenya where 60 villages were randomly assigned to either i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(45 reference statements)
0
9
2
1
Order By: Relevance
“…This result contrasts with the findings of a large trial in Pakistan, which found an increased incidence of diarrhoea and chest indrawing morbidity in MNP-supplemented children (Soofi et al, 2013) but supports the results of other trials that evaluated the impact of MNP on morbidity outcomes (Lemaire et al, 2011;Osei et al, 2015;Sharieff, Bhutta, Schauer, Tomlinson, & Zlotkin, 2006;Suchdev et al, 2016). Most of the latter studies even reported lower risk of diarrhoea (Lemaire et al, 2011;Osei et al, 2015;Suchdev et al, 2016). In our study, the increase in diarrhoea prevalence may be an indication of side-effects of the supplements, which seemed to be mitigated due to the intensive counselling on the use of MNP and appropriate complementary feeding.…”
Section: Morbiditycontrasting
confidence: 76%
“…This result contrasts with the findings of a large trial in Pakistan, which found an increased incidence of diarrhoea and chest indrawing morbidity in MNP-supplemented children (Soofi et al, 2013) but supports the results of other trials that evaluated the impact of MNP on morbidity outcomes (Lemaire et al, 2011;Osei et al, 2015;Sharieff, Bhutta, Schauer, Tomlinson, & Zlotkin, 2006;Suchdev et al, 2016). Most of the latter studies even reported lower risk of diarrhoea (Lemaire et al, 2011;Osei et al, 2015;Suchdev et al, 2016). In our study, the increase in diarrhoea prevalence may be an indication of side-effects of the supplements, which seemed to be mitigated due to the intensive counselling on the use of MNP and appropriate complementary feeding.…”
Section: Morbiditycontrasting
confidence: 76%
“…Their predictive value is often limited by infection, as most iron biomarkers act as acute‐phase‐proteins. To bypass this confounding effect, some studies adjust their cut‐off values using inflammatory markers (C‐reactive protein or alpha ‐1‐acid glycoprotein) as correcting factors (Esan et al , ; Le Nguyen Bao et al , ; Suchdev et al , ), whereas others have made use of iron biomarkers that are less affected by inflammation (e.g. serum transferrin receptor, zinc protoporphyrin) (Wander et al , ).…”
Section: Iron Statusmentioning
confidence: 99%
“…8 Alternatively, because of a saturation of water treatment marketing in the population, its use may have plateaued. 8,[40][41][42] Finally, it is possible that lack of product acceptability might have influenced uptake by mothers. We did not collect data on acceptability of WaterGuard, but it is possible that issues of taste, product cost, or beliefs that water did not need to be treated may have limited use; similar barriers have been noted in other studies.…”
Section: Discussionmentioning
confidence: 99%